Manufacturing System Configuration: Flexibility Analysis For automotive Mixed-Model Assembly Lines. Issue 3 (2015) - Lafou, M.; Mathieu, L.; Pois, S.; Alochet, M.
Abstract: Today's competitive and highly volatile markets are redefining the way manufacturing systems are designed. To meet the requirements of their customers, industries have to manage the wide variety that affects their entire production system in terms of processes, products and resources. Manufacturing system configuration has profound impact on the performance of the system in terms of productivity, flexibility and cost. To cope with production system configuration responsiveness, several flexibility measures were introduced. The purpose of this research work is to make an overview of the existing configuration flexibility factors and to propose a heuristic to deal with automotive mixed-model assembly line (MMAL) specificities. A short case study from the automotive industry is presented.